(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2020)
The article is divided into two parts. The first offers an updated panoramic overview of the Celtiberian language (definition, classification and characteristics) and epigraphic culture (Celtiberian literacy, writing systems, types of inscriptions, corpora). In a second part, the challenges posed in the immediate future in the mentioned aspects are outlined.